Meiosis evolves: adaptation to external and internal environments. Issue 2 (15th June 2015) - Bomblies, Kirsten; Higgins, James D.; Yant, Levi
Summary: Meiosis is essential for the fertility of most eukaryotes and its structures and progression are conserved across kingdoms. Yet many of its core proteins show evidence of rapid or adaptive evolution. What drives the evolution of meiosis proteins? How can constrained meiotic processes be modified in response to challenges without compromising their essential functions? In surveying the literature, we found evidence of two especially potent challenges to meiotic chromosome segregation that probably necessitate adaptive evolutionary responses: whole‐genome duplication and abiotic environment, especially temperature. Evolutionary solutions to both kinds of challenge are likely to involve modification of homologous recombination and synapsis, probably via adjustments of core structural components important in meiosis I. Synthesizing these findings with broader patterns of meiosis gene evolution suggests that the structural components of meiosis coevolve as adaptive modules that may change in primary sequence and function while maintaining three‐dimensional structures and protein interactions. The often sharp divergence of these genes among species probably reflects periodic modification of entire multiprotein complexes driven by genomic or environmental changes. We suggest that the pressures that cause meiosis to evolve to maintain fertility may cause pleiotropic alterations of global crossover rates. We highlight several important areas for future research. Contents Summary 306 I. Introduction 306 II. Whole‐genome duplication and the evolutionary adjustment of meiosis 307 III. Environment as a driver of meiotic evolution 312 IV. Broader evolutionary dynamics 317 V. Summary and conclusions 318 Acknowledgements 319 References 319